Reisolation and NMR characterization of the satratoxins G and H. (12th December 2019) - Hudson, Daniel; Singh, A. Jonathan; Lewis, Andrew R.; Sulyok, Michael; Hinkley, Simon F.R.
Abstract: The exquisitely cytotoxic macrolides, satratoxins G and H, have been reisolated from a solvent extract of a rice culture inoculated with Stachybotrys chartarum to be used as high‐purity reference compounds for analytical analyses. Extensive chromatographic separation realized the compounds that were fully recharacterized in two solvents by 1D‐ and 2D‐NMR spectroscopy, revealing some discrepancies in the nuclear magnetic resonance (NMR) data as compared with the previously reported values found in the literature. Detailed spectra are provided in order to aid future identification and dereplication. Abstract : The macrocyclic tricothecenes satratoxin G and H are exquisitely cytotoxic fungal metabolites produced by Stachybotrys chartarum . Continued interest in these potent molecules warranted isolation and spectroscopic characterization to assist with ongoing identification, dereplication, and quantification.